People and Computers XII 1997
DOI: 10.1007/978-1-4471-3601-9_3
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Telephone-Based Interfaces with Earcons

Abstract: Non-speech audio messages called earcons can provide powerful navigation cues in menu hierarchies. However, previous research on earcons has not addressed the particular problems of menus in telephone-based interfaces (TBI's) such as: Does the lower quality of sound in TBI's lower recall rates, can users remember earcons over a period of time and what effect does training type have on recall. An experiment was conducted and results showed that sound quality did lower the recall of earcons. However, redesign of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 7 publications
0
19
1
2
Order By: Relevance
“…The so-called earcons have the highest abstraction level; they do not allow any semantic relation between an event and a sound, but rather assign an arbitrary audio signal to represent an event. Earcons can be designed not only to represent a single item, but also its position in a hierarchical structure (Brewster et al, 1993), either in audio-only interfaces (such as telephone-based interfaces (Brewster, 1997(Brewster, , 1998LePlaˆtre and Brewster, 1998)) or multi-modal interfaces (Brewster et al, 1993;Brewster and Crease, 1999;Vargas and Anderson, 2003). It has been shown that earcons can successfully improve the usability of multi-modal interfaces for mobile use (Pirhonen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The so-called earcons have the highest abstraction level; they do not allow any semantic relation between an event and a sound, but rather assign an arbitrary audio signal to represent an event. Earcons can be designed not only to represent a single item, but also its position in a hierarchical structure (Brewster et al, 1993), either in audio-only interfaces (such as telephone-based interfaces (Brewster, 1997(Brewster, , 1998LePlaˆtre and Brewster, 1998)) or multi-modal interfaces (Brewster et al, 1993;Brewster and Crease, 1999;Vargas and Anderson, 2003). It has been shown that earcons can successfully improve the usability of multi-modal interfaces for mobile use (Pirhonen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Earcons and auditory icons have been used extensively in auditory humancomputer interfaces [19]. Earcons are used to communicate context such as hierarchies [20], depict visual categorisation [21], for menu navigation in graphical user interfaces [22], telephone interfaces [23] and mobile phones [24]. Their scalability allows for creation of intermittent sounds that are used to create cues [25].…”
Section: Problem Formulationmentioning
confidence: 99%
“…[3], [7], and [17] are good examples of the first approach. This line of research usually examines the design of audio menus ("press 1 if you are calling about a current account, press 2 if…") and how to best design input methods when the system is limited to a small keypad and voice.…”
Section: Prior Work In Pc-phone Convergencementioning
confidence: 99%